(untitled) (Global Business Management Review (GBMR), 2019)
The purpose of this paper is to investigate the influence of subjective norms , idolatry and intentions of consumer purchase behaviour of pirated music CDs in Tanzania. In order to empirically test the hypotheses of the study, questionnaires were distributed to 491 users of pirated music CDs in Tanzania. The data from the questionnaires were analyzed using PLS- SEM. The results of the study revealed that subjective norm and intention are positively related to consumer purchase behaviour. On the other hand, idolatry has a negative relationship with purchase behaviour. The results of this study will be useful for marketers, businessman and music promoters when identifying the factors that are to be considered when intending to improve the level of sales among music CDs users in Tanzania. It will also assist the policy makers to come up with policies especially in the area of norms so as to improve the rate of sales. The findings of this study may benefit music marketers, producers and practitioners in their marketing communication to design their music strategies in the Tanzania context.